Formal, non-formal and informal education and innovation: Innovating to educate and educating to innovate (Innovaciones Educativas, 2023)
This paper analyzes the relationship between the educational experience and the innovative person, and studies the influence of this experience on the development of capacities and skills for innovation in the people interviewed. The discussion is based on a qualitative approach, by means of ten interviews with people defined as innovators, located in companies of the food industry in Costa Rica. The experiences of innovators are analyzed with respect to the different types of education and how these allow generating competencies for innovation, that is, whether or not they allow educating to innovate. Among the main findings is the identification, at different levels, of the influence of the formal, non-formal and informal educational process on the development of innovators. This influence is not always positive, as it can appear as a condition that favors the development of innovation capabilities or as a limiting factor, as shown by the experiences of the innovators studied.
Keywords: formal education; non-formal education; informal education; educational innovation